2018
DOI: 10.1037/bul0000141
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of longitudinal associations between substance use and interpersonal attachment security.

Abstract: Substance use has long been associated with close relationship distress. While the direction of influence for this association has not been established, it has often been assumed that substance use is the causal agent and that close relationship distress is the effect. But research seeking to establish temporal precedence in this link has produced mixed findings. Further, theoretical models of substance use and close relationship processes present the plausibility of the inverse pathway—that insecure close rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
80
1
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 156 publications
9
80
1
4
Order By: Relevance
“…Contrary to hypotheses and prior research, we did not find an association between cannabis misuse and discipline or attachment (16,28). Discipline is similar to the construct of parental control which, in the absence of a supportive relationship, is related to adolescent problem behavior (7,18).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to hypotheses and prior research, we did not find an association between cannabis misuse and discipline or attachment (16,28). Discipline is similar to the construct of parental control which, in the absence of a supportive relationship, is related to adolescent problem behavior (7,18).…”
Section: Discussioncontrasting
confidence: 99%
“…Treatments that include a parenting or family component to support the adolescent, reduce family conflict, and increase adaptive behaviors like rule-setting and monitoring show potential for reducing impairment (10,(13)(14)(15). Specifically, characteristics of the parent-adolescent relationship, including warmth, attachment, control, and discipline have been linked to adolescent psychopathology and problem behavior, including substance use (16)(17)(18)(19)(20)(21)(22)(23). In the context of psychiatric disorders, parent-youth relationships can be complicated and a source of frustration and stress (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on psychotic patients showed that being single increases the risk of readmission, while others found that a divorce increases the likelihood of readmission (23). There is a large evidence that SUDs are generally associated with dysfunctional attachment (24). Relational difficulties in SUD are underscored by the fact that divorces are seven times more likely in patients with alcohol addiction than in others (25).…”
Section: Discussionmentioning
confidence: 99%
“…The psychological and developmental literature already contains several excellent reviews that have examined the empirical findings showing the relationship between a variety of measures of attachment and different kinds of addiction (53,54). While it is well accepted that addiction results in the deterioration of the quality of close relationships, Fairbairn's review showed that longitudinal studies have established that attachment insecurity prospectively predicts the development of later substance problems irrespective of the type of measure used.…”
Section: Review Of Attachment Related Predictors Of Addictionmentioning
confidence: 99%